Unexpected Regiochemical Control in the Nugent–RajanBabu Reductive Epoxide Cyclization - Supantanapong, Nantamon; Niman, Scott W.; Vanderwal, Christopher D. (Synthesis, 2025)
The Nugent–RajanBabu reductive epoxide cyclization has become a mainstay of alternative methods to accomplish classical, biomimetic, cationic polyene cyclizations. In most cases, the regiochemical control for the formation of decalins and perhydrophenanthrenes is exquisite, mirroring that obtained in cationic reactions, to the point where the 6-endo reactivity is anticipated even in the face of potential 5-exo processes. In our studies toward complex, polyoxygenated terpenoid natural products, we had cause to evaluate the reactions of α-alkoxy epoxides in these types of reactions, and we were surprised to uncover a means to control 6-endo vs. 5-exo reactions based on the size of the protecting group on the α-oxygen. This knowledge opens up the possibility of rapid syntheses of highly oxygenated cyclopentane systems, in addition to the expected decalin scaffolds.
Keywords: Cyclizations; Radical; Epoxide; Terpenoids; Total synthesis; Regiocontrol